Pengaruh Fixed Asset Turnover, Return On Asset, Current Ratio, Dan Total Asset Turnover Terhadap Harga Saham Pada Sektor Indutsri Dasar Dan Kimia (Basic Indutry And Chemicals) Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2017-2020 - Benny R.M Nainggolan; Tiara Rufita Hutapea; Evi Pardede; Rusnia Winata Sianturi; Cindy Veronika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The research that test the effect of Fixed Asset Turnover, Return On Asset, Current Ratio, and Total Asset Turnover on stock prices in the Basic Industry and Chemicals Sector was conducted either simultaneously or partially used non-probability sampling technique with a quantitative research and also a classical assumption test that obtained sixty (60) companies as a sample in the basic industrial and chemical sectors is obtained. The value of Ftable with 0.05 significance, namely 2.56 with Fcount > Ftable so that it is concluded that the independent variables have a substantial effect on the dependent variableâ€. T-Test resultâ€™s (partial test) are â€œFAT (X1) and CR (X3) do not affect stock prices (Y). ROA (X2) states a negative affect on stock prices (Y). TATO (X4) defines a positive affect on stock prices (Y). Keywords: Fixed Asset Turnover (FAT), Return On Asset (ROA), Current Ratio (CR), and Total Asset Turnover (TATO)